Response to the ‘Consensus Statement of the Working Group on Roman Catholic Approaches to Determining Appropriate Critical Care’ - Hauerwas, Stanley (Christian bioethics, 2001)
Stanley Hauerwas; Response to the ‘Consensus Statement of the Working Group on Roman Catholic Approaches to Determining Appropriate Critical Care’, Christian bi